A broadband hybrid GaN cascode low noise amplifier for WiMax applications. Issue 10 (4th September 2018) - Jarndal, Anwar H.; Bassal, Amer M.
Abstract: This article reports a Microstrip design for low noise amplifier (LNA) using a packaged commercial GaN‐on‐SiC high electron mobility transistor (HEMT). A cascode configuration with an inter‐stage matching and an independent biasing technique was used. A lumped elements design was first developed, analyzed, and simulated in ADS. Then the design was implemented using microstrip technology and simulated using the momentum EM simulation in ADS. The LNA is easy to fabricate, has a low cost, and can be easily modified for other applications. The proposed GaN LNA showed a gain of 13.5 dB with a noise figure (NF) of 3 dB from 2.8 to 3.8 GHz.